Disabled Readers Insight, Assessment, Instruction - International Reading Association, Newark, DE.; Sawyer, Diane J.; International Reading Association, Newark, DE. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Focusing on helping teachers to understand and help children who have reading disabilities, the 13 papers in this volume were prepared by practitioners at various levels from public school, community, and university settings. The papers included in part one offer insights into the concomitant aspects of reading difficulties. Specific topics discussed are perceptual bases for reading difficulties, the disabled adolescent reader, reading disability and family dynamics, and dyslexia. The papers in part two deal with aspects of assessment and planning for instruction. Topics covered are kindergarten diagnosis and training, reading diagnosis in the classroom, informal assessment of comprehension, adaptive assessment for nonacademic secondary reading, and psychoeducational diagnosis as inservice education. The papers in section three offer suggestions for instructional practices. Specific topics covered are practical suggestions for remedial teachers, sentence combining practice as an aid to reading comprehension, myopia, and teaching reading to the hearing impaired child. (FL)
Availability: International Reading Association, 800 Barksdale Rd., P.O. Box 8139, Newark, DE 19711 (Order No. 490, $3.50 member, $5.00 non-member).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary Secondary Education; Evaluation Methods; Inservice Education; Learning Disabilities; Reading Comprehension; Reading Diagnosis; Reading Difficulty; Reading Instruction; Reading Research; Remedial Programs; Remedial Reading; Teaching Methods; Collected Works, General; Guides, Classroom -- Teacher; Books